PERAN INOVASI LAYANAN DALAM MENINGKATKAN KEPUASAN NASABAH PADA BANK SYARIAH DI ERA DIGITAL - Alvia Auliah; Miftahul Jannah; Muh Fajar Ali; Kamaruddin, Kamaruddin (Cahaya Ilmu Bangsa, 2024)
This research aims to analyze the role of service innovation in increasing customer satisfaction at Islamic banks in the digital era. Service innovation is one of the key factors in the banking industry, especially with rapid technological developments and increasing customer needs for fast, safe and easily accessible services. In the context of Islamic banks, service innovation does not only rely on technological advances, but must also remain in line with sharia principles. This research uses a quantitative approach with data collected through surveys of sharia bank customers who use digital services such as internet banking, mobile banking and sharia-based applications. The research results show that service innovation, such as the development of user-friendly mobile applications, QR Code-based payment systems, and digital education regarding sharia products, contribute significantly to increasing customer satisfaction. In addition, trust factors and conformity with sharia values also strengthen the relationship between service innovation and customer satisfaction.